The Teachers' Level of ICT in English Teaching Practices at SMK Negeri 2 Makassar - Febryanti, Muthmainnah; Bte Abdul, Nurdevi; AM, St. Asmayanti (Journal of Computer Interaction in Education, 2019)
This study aimed to determine the types of information and communication technology (ICT) used by teachers to teach English at SMK Negeri 2 Makassar and the level of use of information and communication technology (ICT) in teaching English. Data was collected in February 2022 from 2 tenth and eleventh grade teachers at SMK Negeri 2 Makassar. This study used a qualitative descriptive method, and the instruments used were observation and interviews. Observation was used to observe and interview the tenth and eleventh grade English teachers at SMK Negeri 2 Makassar. Based on the findings and discussion of this study, the researcher concludes that an English teacher uses two types of ICT applications to teach as the current implementation of ICT in education. These types not only help the English teacher but also help the students not to be boring in the learning process. Based on the English teacher's answer, the teacher said that the teaching process is more innovative and saves time.Before showing material using the ICT application, an English teacher in grades first and second of SMKN 2 Makassar has several preparations, namely the first is the introduction of ICT, the second is to prepare the material using the LCD and the third is to ask questions to students about learning the material.The next finding is that the researcher finds that the level of ICT use for English teachers at SMK Negeri 2 Makassar is at LEVEL 3, namely Pedagogy.